5S Lean Tool, Value Stream Mapping and Warehouse Performance: Conceptual Framework - Mohd Fadzil Harun; Nurul Fadly Habidin; Nor Azrin Md Latip (International Journal of Supply Chain Management, 2019)
This study propose the conceptual framework the relationship between 5S lean tool, value stream mapping (VSM) and warehouse performance (WP) among Malaysian manufacturing industry. The data collected will be analyzed using two packages statistical software. The Statistical Package for Social Sciences (SPSS) software will be employed to analyze the reliability test and descriptive analysis. The Structural Equation Modeling (SEM) technique will also be employed in future study using AMOS software to investigate the relationship between the developed conceptual frameworks through the path analysis by the SEM approach. Thus, the implication of this study is seen as important and useful in increasing knowledge, propose dimensions, and propose conceptual framework for 5S lean tool and VSM are initiatives to improve WP among Malaysian manufacturing industry. Finally, it can be provided as a guideline and reference for the manufacturing practitioners and academicians